Calculation Model and Decoupling Coefficient Sensitivity Study of Periphery Hole for Eccentric Decoupled Charge in Highway Tunnels - Yuanqing Wang; Junfeng Liu (Shock and Vibration)
On the basis of the eccentric decoupled charge form on site and borehole concentric decoupled computational theory, the calculation model of eccentric decoupling charge would be established in the present study. The calculation model takes into account the influence factors such as damage to the surrounding rock, air, and water decoupled media. Besides, based on the proposed calculation model, blasting effect of a small-diameter EJ-102 emulsion explosive is calculated by using ANSYS LS-DYNA. The influence of decoupling coefficient, different rock grade, and different RQD value on blasting effect is obtained by sensitivity analysis of the simulated parameters. Then the calculated results are compared with the empirical results. The blasting parameters of fractured rock mass are also optimized by numerical simulation.